Utilization of IoT for Measuring Hydrogen Production in a Photovoltaic-Solid Polymer Electrolyte (PV-SPE) System - Muhida, Riza; Riza, Muhammad; Harsoyo, Agung; Murwadi, Haris; Legowo, Ari (Master Program in Mechanical Engineering, Gunadarma University, 2025)
The integration of the Internet of Things (IoT) technology into a Photovoltaic-Solid Polymer Electrolyte (PV-SPE) system offers an innovative solution for monitoring and optimizing hydrogen production in real time. This study presents the design and implementation of an IoT-based monitoring system for a PV-SPE hydrogen production system, utilizing ESP32 microcontrollers to collect and transmit critical operational data, including voltage, current, temperature, humidity, and hydrogen flow rate, to the Adafruit IO cloud platform. A Maximum Power Point Tracking (MPPT) controller was employed to optimize power transfer from the solar panel to the SPE electrolyzer, ensuring maximum efficiency in the electrolysis process. Experimental results confirmed that hydrogen production rates correlate directly with PV power output, with the IoT-enabled system providing efectively measurement compared to conventional methods. The system demonstrated stable data acquisition, real-time monitoring, and remote accessibility, allowing users to track hydrogen generation performance efficiently. This study concludes that the combination of IoT, renewable energy, and electrolysis technology enhances the efficiency, and scalability of hydrogen production systems